2018
DOI: 10.1016/j.ijdevneu.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulphate induces preconditioning in preterm rodent models of cerebral hypoxia‐ischemia

Abstract: We have established a postnatal day 4 rat model of HI for the study of preterm brain injury. MgSO provides a marked preconditioning protection both in postnatal day 4 rats and in postnatal day 5 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(74 reference statements)
3
6
0
Order By: Relevance
“…In conclusion, we showed for the first time that enhanced autophagy could mediate cell death in a premature model of excitotoxic brain damage. Autophagy inhibition in this severe model is very promising since the protective effect obtained is similar or even better to other previously described neuroprotectants such as caspases inhibitors 69 , erythropoietin 70 , 71 , BDNF 72 , 73 , melatonin 74 or magnesium sulfate 75 , 76 . Interestingly, we recently demonstrated that autophagy is enhanced in dying neurons in the ventrolateral nucleus of the thalamus and the lentiform nucleus of term newborns with severe HIE 31 , 60 .…”
Section: Discussionsupporting
confidence: 72%
“…In conclusion, we showed for the first time that enhanced autophagy could mediate cell death in a premature model of excitotoxic brain damage. Autophagy inhibition in this severe model is very promising since the protective effect obtained is similar or even better to other previously described neuroprotectants such as caspases inhibitors 69 , erythropoietin 70 , 71 , BDNF 72 , 73 , melatonin 74 or magnesium sulfate 75 , 76 . Interestingly, we recently demonstrated that autophagy is enhanced in dying neurons in the ventrolateral nucleus of the thalamus and the lentiform nucleus of term newborns with severe HIE 31 , 60 .…”
Section: Discussionsupporting
confidence: 72%
“…Although this study focuses primarily on the effect of SFA on cortical brain cells, perinatal brain injury can take place, often simultaneously, in both gray and white matter [7][8][9]. A common cause for perinatal brain injury is HI induced rise in ROSs which lead to cell death through activation of apoptotic receptors or proteins, and mitochondrial dysfunction.…”
Section: Plos Onementioning
confidence: 99%
“…Excitotoxicty against oligodendrocytes works also by extracellular glutamate accumulation and results in an increase of ROSs causing oxidative stress. These processes are detrimental to the brain; by damaging oligodendrocytes they specifically reduce or attenuate the myelination process, thereby creating vulnerable neurons [2,7,9,30,31]. With all of these cellular constituents present in the co-culture, it is more likely to thrive compared to isolated neuron or astrocyte cultures; and their response to effects of SFA is more representative of what an in vivo response may look like.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the options from the classes of drugs already being tested in models of EoP, we find that, despite many compounds being tested (with mixed results), most have not considered outcomes in the GM. There are some notable exceptions, such as MgSO 4 pre-treatment in a rat model of preterm HI (modeling antenatal treatment in at-risk mothers), significantly reduced tissue loss in the hippocampus and striatum and were associated with reduced neurological injury score (219). MgSO 4 has also been tested in a sheep model of perinatal asphyxia, reporting reduced seizure burden, but worse WM outcomes and no GM neuropathology (189).…”
Section: Gray Matter Targetsmentioning
confidence: 99%